Development of a mathematics module on circle material based on the small group discussion model - Lumbantoruan, Jitu Halomoan; Ditasona, Candra (Intelektual Pustaka Media Utama, 2024)
This research aims to produce a mathematics module on circle material based on the small group discussion model to improve learning outcomes. The fact is that there are 48% of students who get low mathematics learning outcomes. Another fact is that at the high school level, 62% of students in circle material scored below the minimum completeness criteria. Urgent development research was carried out to produce circular module products. The method in this research is research and development (RD). The subjects and objects of the research were high schools and there were 32 students. Data collection techniques, material expert instruments, teachers, and student data were also obtained from the results of student pre-tests and post-tests. The data was analyzed by adding up all the assessment scores on the instruments adding up the test results and averaging the individual and classical scores. The results, and assessment of all module components by material experts, mathematics teachers, small group trials, and large group trials were 88.29%, 90.45%, 93.50%, and 92.10% in the very good category. The average score of students' post-test results is 87.50. Conclusion, this circle module can improve student learning outcomes significantly.